Implementasi Sistem Monitoring Tanaman Hidroponik Menggunakan Metode Fuzzy Sugeno - Tegar Palyus Fiqar; Fitriani Fitriani; Riska Kurniyanto Abdullah (Jurnal Teknologi Informasi dan Multimedia, 2023)
Farming using hydroponic systems has emerged as an effective alternative to address the problem of limited agricultural land. However, hydroponic farming requires strict maintenance and control. In light of these challenges, the development of monitoring technology is necessary to assist in monitoring and controlling hydroponic systems. The development of a monitoring system is carried out to address the challenges of maintenance and control in hydroponic farming through the development of effective and accurate monitoring technology, thus enhancing the overall productivity and success of hydroponic plant cultivation. This study aims to develop a monitoring system using Arduino Mega 2560, Wemos D1 R2, E201 sensor, DHT22 sensor, HC-SR04 sensor, and BH1750 sensor. In this research, the fuzzy logic method was applied to generate outputs for the water pump actuator, pH up pump, and pH down pump. The HC-SR04 and E201 sensor data served as fuzzy inputs, while the Arduino Mega 2560 functioned as the fuzzy data processor, and the Wemos D1 R2 was responsible for sending data to the server via the internet. The data successfully stored in the server's database would be displayed on the monitoring dashboard. The HC-SR04 sensor testing results showed an average %error of 0% and an accuracy of 100%. The E201 sensor exhibited an average %error of 0.07% and an accuracy of 99.33%. The DHT22 sensor had an average %error of 0.05% and an accuracy of 99.49% for temperature data, while for humidity data, it had an average %error of 2.58% and an accuracy of 75.23%. The BH1750 sensor had an average %error of 0.13% and an accuracy of 99.66%. The results of this study demonstrate that the hydroponic plant monitoring system using the described devices and methods can be implemented successfully.